2015
DOI: 10.1177/1528083715577936
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cenosphere addition on the mechanical properties of jute-glass fiber hybrid epoxy composites

Abstract: Cenosphere is a ceramic-rich industrial waste produced during burning of coal in thermal power plants. This study deals with the effect of cenosphere as particulate filler on mechanical behaviour of woven jute-glass hybrid composites. The hybrid composite consists of jute and glass fiber as reinforcement and epoxy as matrix. The conventional hand lay-up technique is used to prepare composite specimens. Cenosphere of different weight percentage (5, 10, 15 and 20 wt%) was added to the hybrid composite. The sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 21 publications
4
20
0
Order By: Relevance
“…Ramakrishnan et al [8] had experimented on the effect of nano-clay addition on the mechanical and water absorption behaviour of jute fibre-reinforced epoxy composites and found that 5% nano clay fillers with 5% NaOH treated fibres had exhibited higher tensile, flexural, and impact strengths [8]. Dalbehera and Acharya [9] had investigated on the effect of the addition of cenosphere on the mechanical properties of jute-glass fibre hybrid epoxy composites and found that addition of 15% of waste ceramic cenosphere had improved the tensile flexural and interlaminar shear strength when compared to the other laminates. Arpitha et al had studied the hybridization effect of fibre/filler-based composites that had been manufactured using vacuum bagging method.…”
Section: Introductionmentioning
confidence: 99%
“…Ramakrishnan et al [8] had experimented on the effect of nano-clay addition on the mechanical and water absorption behaviour of jute fibre-reinforced epoxy composites and found that 5% nano clay fillers with 5% NaOH treated fibres had exhibited higher tensile, flexural, and impact strengths [8]. Dalbehera and Acharya [9] had investigated on the effect of the addition of cenosphere on the mechanical properties of jute-glass fibre hybrid epoxy composites and found that addition of 15% of waste ceramic cenosphere had improved the tensile flexural and interlaminar shear strength when compared to the other laminates. Arpitha et al had studied the hybridization effect of fibre/filler-based composites that had been manufactured using vacuum bagging method.…”
Section: Introductionmentioning
confidence: 99%
“…The observed results were proof of other research works involving fiber/ filler particulate-reinforced epoxy composites. 43,44 However, the tensile properties decreased beyond 10% of the filler addition. The decrease in the tensile properties of the 15% composites was probably due to the poor interaction between the filler and the matrix.…”
Section: Mechanical Properties Of the Compositementioning
confidence: 99%
“…The results showed that the inclusion of cenosphere as filler materials in vinylester composites will increase the wear resistance of the composite significantly. Soma Dalbehera et al [11] deals with the effect of cenosphere as particulate filler on mechanical behaviour of woven jute-glass hybrid composites. The hybrid composite consists of jute and glass fiber as reinforcement and epoxy as matrix.…”
Section: Effect Of Process Parameters On Mechanical Characteristicsmentioning
confidence: 99%